Good Amil Governance (GAG) on ZCP In the study of the Zakat Fatwa of Muhammadiyah, NU and MUI, and its implementation in LAZ - Hasanah, Erni Juliana (Center of Strategic Studies (PUSKAS) BAZNAS, 2024)
This article analyzes Good Amil Governance (GAG) at Amil Zakat Institutions (LAZ) in a study of zakat fatwas produced by Islamic community organizations in Indonesia and its relationship with the Zakat Core Principle (ZCP) and its application to Amil Zakat Institutions. This study used qualitative methods and data from interviews, field observations, and literature reviews. The results show that the zakat fatwas reflects the thinking that developed and was adopted by the ulama at that time, was a response to societal problems, and followed the developing social, economic, and political context. Even though the fatwa is not binding, its role as an operational guide for zakat management is vital. The findings of this research: First, the zakat fatwa related to GAG has logical reasoning that is in line with state regulations and the ZCP; second, the fatwa is in line with the government's political interests, especially regarding the authority to manage zakat; third, the fatwa ends the debate about Ulil Amri in the management of zakat; and the four ZCPs are well implemented in LAZ. The zakat fatwa shows the increasing role of Islamic organizations in managing zakat. Research with this theme is rare.